2015
DOI: 10.1021/acschembio.5b00671
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Specific Binding Proteins to Photoaffinity Linkers for Efficient Deconvolution of Target Protein

Abstract: Photoaffinity-based target identification has received recent attention as an efficient research tool for chemical biology and drug discovery. The major obstacle of photoaffinity-based target identification is the nonspecific interaction between target identification probes and nontarget proteins. Consequently, the rational design of photoaffinity linkers has been spotlighted for successful target identification. These nonspecific interactions have been considered as random events, and therefore no systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 40 publications
1
66
0
3
Order By: Relevance
“…Photoaffinity based target ID overcomes those limitations by UV induced covalent bond generation between small molecule and interacting proteins [68]. The covalent bonding secure small molecule-protein interaction in various experimental conditions [69, 70]. Moreover, weak binding or low abundant target proteins can be tractable from huge amount of other non-target proteins in cell lysate [71].…”
Section: Photoaffinity Based Target Id Probementioning
confidence: 99%
“…Photoaffinity based target ID overcomes those limitations by UV induced covalent bond generation between small molecule and interacting proteins [68]. The covalent bonding secure small molecule-protein interaction in various experimental conditions [69, 70]. Moreover, weak binding or low abundant target proteins can be tractable from huge amount of other non-target proteins in cell lysate [71].…”
Section: Photoaffinity Based Target Id Probementioning
confidence: 99%
“…36 top). They reported [102] the PAL of photo-affinity linkers containing three photoactivatable moieties, DA, BP and AA. They found that each photo-affinity group binds to a different set of proteins in a structure-dependent manner, in contrast to previous beliefs.…”
Section: Comparative Probesmentioning
confidence: 99%
“…Figure reproduced from ref. [102] with permission from ACS publication. ( Bottom ) Schematic illustration of the molecular shape-dependence of protein labeling.…”
Section: Comparative Probesmentioning
confidence: 99%
“…The concept of photoaffinity labeling (PAL) was originally introduced by Frank Westheimer in the early 1960s, 1 and since then it has gradually emerged as a powerful tool for the identication and localization of targets and corresponding interaction sites in complicated biological systems, 2 especially in some cases such as low-abundance proteins and low-affinity interactions that fail to survive disruptive washing steps. 3,4 Four common types of photoreactive group are used in PAL, namely, aryl azides (AZs), benzophenones (BPs), diazirines (DAs) 5,6 (New) and 2-aryl-5-carboxytetrazoles (ACTs), 7,8 which are classied in accordance with their photochemically generated reactive species, namely, nitrenes, diradicals, carbenes and carboxy-nitrile imines. In addition, some photoreactive components of natural molecules that can undergo photolysis to form highly reactive intermediates, such as steroid enones (e.g., pyrones and pyrimidones 9 ), various aryl chlorides, and several thioethers, have been utilized as probes to avoid complications associated with fully synthetic probes.…”
Section: Introductionmentioning
confidence: 99%